Saving and Consumption When Children Move Out - Alexander Klos; Simon Rottke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Based on the German Socio-economic Panel (SOEP), we show that household consumption drops and saving rises significantly within four years after a child moves out of a household. Per capita consumption of parents is approximately leveled up to that of childless peers after all children are gone. We conclude with respect to the adequacy of saving rates that calibrated life-cycle models assuming a smoothing of per capita consumption for parents with children in the household underestimate the wealth needed to smooth consumption in the long run.
Keywords: D12; D14; D10; 330